cDNA cloning and characterization of the carboxylesterase pxCCE016b from the diamondback moth, Plutella xylostella L. - Zhen-di HU; Xia FENG; Qing-sheng LIN; Huan-yu CHEN; Zhen-yu LI; Fei YIN; Pei LIANG; Xi-wu GAO (Journal of Integrative Agriculture, 2016)
Carboxylesterase is a multifunctional superfamily and can be found in almost all living organisms. As the metabolic enzymes, carboxylesterases are involved in insecticides resistance in insects for long time. In our previous studies, the enhanced carboxylesterase activities were found in the chlorantraniliprole resistance strain of diamondback moth (DBM). However, the related enzyme gene of chlorantraniliprole resistance has not been clear in this strain. Here, a full-length cDNA of carboxylesterase pxCCE016b was cloned and exogenously expressed in Escherichia coli at the first time, which contained a 1693 bp open reading frame (ORF) and encoded a protein of 542 amino acids. Sequence analysis showed that this cDNA has a predicted mass of 61.56 kDa and a theoretical isoelectric point value of 5.78. The sequence of deduced amino acid possessed the classical structural features: a type-B carboxylesterase signature 2 (EDCLYLNVYTK), a type-B carboxylesterase serine active site (FGGDPENITIFGESAG) and the catalytic triad (Ser186, Glu316, and His444). The real-time quantitative PCR (qPCR) analysis showed that the expression level of the pxCCE016b was significantly higher in the chlorantraniliprole resistant strain than in the susceptible strain. Furthermore, pxCCE016b was highly expressed in the midgut and epidermis of the DBM larvae. When the 3rd-instar larvae of resistant DBM were exposed to abamectin, alpha-cypermethrin, chlorantraniliprole, spinosad, chlorfenapyr and indoxacarb insecticides, the up-regulated expression of pxCCE016b was observed only in the group treated by chlorantraniliprole. In addition, recombinant vector pET-pxCCE016b was constructed with the most coding region (1 293 bp) and large number of soluble recombinant proteins (less than 48 kDa) were expressed successfully with prokaryotic cell. Western blot analysis showed that it was coded by pxCCE016b. All the above findings provide important information for further functional study, although we are uncertainty whether the pxCCE016b gene is actually involved in chlorantraniliprole resistance.